(untitled) (Damascus University Journal of arts and humanities sciences, 2026)
The study aims to identify podcasts uses and gratifications for the Syrian audience through a measurement that combines the gratifications of both content and medium. In addition, the study looks to quantify the impact of the demographic variables on the Syrian audience’s uses and gratifications using a sample of (242) participants. The results show that (136) participants use this service; (56%) of the study sample. The service use of those is low (50%), dependent on YouTube as a service provider via their mobile phones (88.97%), and takes place during the evening (66.2%). The topic of personal skills development has been the most prominent to (25.74%) of the sample, while favoring the converse style (49.26%), and a presentation in Arabic (87.50%). There is a high rate of gratifications derived from using podcast services among the participants (98.53%). Gratifications related to medium have surpassed those related to content. Furthermore, there is a moderately positive correlation between the rate of podcast service use and the achieved gratifications. There are no significant differences among the sample members in relation to podcast uses and gratifications according to the variables of age and gender. Nonetheless, the study shows significant differences on this according to the variable of education, in favour of the secondary level education.